MANAGEMENT OF YEH AYA HULU DAM POTENTIAL AS A COMMUNITY-BASED NATURAL TOURISM ATTRACTION IN SENGANAN VILLAGE, PENEBEL SUB-DISTRICT, TABANAN DISTRICT - Ni Putu Shopia Desita Rembrantari; I Ketut Arta Widana; Ni Made Rai Kristina (UHN IGB Sugriwa Denpasar, 2023)
Yeh Aya Hulu Dam has the potential to be developed into a natural tourist attraction in Senganan Village. The potential is inadequate, the village that still does not pay attention to this potential causes the Yeh Aya Hulu Dam to be not managed properly and the overall potential has not been explored. This study aims to determine the management of Yeh Aya Hulu's potential as a community-based natural tourism attraction. This research uses qualitative descriptive analysis methods, using Tourism Attraction theory 6A, Tourism Management theory and Tourism Impact theory. Data collection techniques are carried out by observation, interviews, literature studies, and documentation. The data obtained is then analyzed using three data analysis models, namely data reduction, data presentation, and conclusions. This study uses a qualitative descriptive analysis method, using the theory of Tourist Attraction 6A, Tourism Management, and Tourism Impact. Data collection techniques were collected through observation, interviews, literature studies, and documentation. The data obtained were then analyzed using three data analysis models: data reduction, data presentation, and conclusion drawing. The results showed that the potential of Bendungan Yeh Aya Hulu as a natural tourist attraction with the 6A theory is that attractions consist of natural, artificial, and cultural tourist attractions with good access and are easy to reach by tourists. Facilities include a parking area for two-wheeled vehicles while for four-wheeled vehicles, parking on the side of the road, toilets and changing rooms that still need to be put up to standard, and stalls. Tourists can enjoy views of the rice fields, swim, play tube tubing, and buy food. Additional services that still need to be available and tour packages will be planned in the future. The management of Bendungan Yeh Aya Hulu as a natural tourist attraction holds the concept of CBT (Community-Based Tourism) which applies the functions of tourism management, including planning, organizing, actuating, monitoring, and motivation. The impact of managing Bendungan Yeh Aya Hulu as a natural tourist attraction on the community is divided into environmental, socio-cultural, and economic impacts.